Experiential Knowledge of Mental Health Professionals. Service Users’ Perceptions - Karbouniaris, Simona; Wilken, Jean Pierre; Weerman, Alie; Abma, Tineke (European Journal of Mental Health, 2022)
Introduction: Nowadays the Western mental health system is in transformation to recovery-oriented and trauma informed care in which experiential knowledge becomes incorporated. An important development in this context is that traditional mental health professionals came to the fore with their lived experiences. From 2017 to 2021, a research project was conducted in the Netherlands in three mental health organizations, focussing on how service users perceive the professional use of experiential knowledge. Aims: This paper aims to explore service users’ perspectives regarding their healthcare professionals’ use of experiential knowledge and the users’ perceptions of how this contributes to their personal recovery. Methods: As part of the qualitative research, 22 service users were interviewed. A thematic analysis was employed to derive themes and patterns from the interview transcripts. Results: The use of experiential knowledge manifests in the quality of a compassionate user-professional relationship in which personal disclosures of the professional’s distress and resilience are embedded. This often stimulates users’ recovery process. Conclusions: Findings suggest that the use of experiential knowledge by mental health professionals like social workers, nurses and humanistic counselors, demonstrates an overall positive value as an additional (re)source.